Chromatographic purification of antimony for accurate isotope analysis by MC-ICP-MS. Issue 7 (1st June 2020) - Liu, Jianfeng; Chen, Jiubin; Zhang, Ting; Wang, Yina; Yuan, Wei; Lang, Yunchao; Tu, Chenglong; Liu, Liangzhi; Birck, Jean-Louis
Abstract : A new purification approach is reported for the highly precise and accurate determination of Sb isotope ratios in geological samples. Abstract : A two-step method for purifying antimony (Sb) from geological samples for accurate measurement of Sb isotopic composition using multi-collector inductively coupled plasma mass spectrometry (MC-ICP-MS) was developed. Sb was separated from the matrix using two successive chromatographic columns loaded with AG 1-X4 and AG 50W-X8 resin, respectively. The separation method was calibrated using geological samples by assessing the extraction yield and the reproducibility of the measured isotopic composition, and resulted in a relatively low procedure blank and better recovery (98.7% ± 5.6%, n = 8, 2SD) compared to previous studies. The validation of the whole protocol, together with instrumental analysis, was confirmed by the investigation of the matrix effect and the result of a standard addition experiment. A combined sample-standard bracketing and external normalization (SSB-EN) method using cadmium (Cd) as an internal element was used for mass bias correction, which gave a reproducibility better than 0.04‰ (2SD). A variation of 0.29‰ of the δ 123 Sb value (relative to the NIST SRM 3102a standard) was observed in artificial and geological samples, implying the potential application of Sb isotopes in various environments.